2002
DOI: 10.1074/jbc.m109354200
|View full text |Cite
|
Sign up to set email alerts
|

RGC-32 Increases p34CDC2 Kinase Activity and Entry of Aortic Smooth Muscle Cells into S-phase

Abstract: Proliferation of aortic smooth muscle cells contributes to atherogenesis and neointima formation. Sublytic activation of complement, particularly C5b-9, induces cell cycle progression in aortic smooth muscle cells. RGC-32 is a novel protein that may promote cell cycle progression in response to complement activation. We cloned human RGC-32 cDNA from a human fetal brain cDNA library. The human RGC-32 cDNA encodes a 117-amino acid protein with 92% similarity to the rat and mouse protein. Human RGC-32 maps to chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 37 publications
1
153
1
Order By: Relevance
“…RGC-32 was first identified in oligodendrocytes in response to complement activation (38). It is a 14-kDa protein expressed in many adult human tissues including heart, brain, liver, skeletal muscle, placenta, kidney, and pancreas (39), and it is overexpressed in colon cancer and many tumors (40). Functionally, RGC-32 has been shown to play a role in cell cycle activation.…”
Section: Resultsmentioning
confidence: 99%
“…RGC-32 was first identified in oligodendrocytes in response to complement activation (38). It is a 14-kDa protein expressed in many adult human tissues including heart, brain, liver, skeletal muscle, placenta, kidney, and pancreas (39), and it is overexpressed in colon cancer and many tumors (40). Functionally, RGC-32 has been shown to play a role in cell cycle activation.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of RGC32 induces quiescent aortic smooth-muscle cells to enter into the S-phase (Badea et al, 2002). Others have reported that RGC32 physically associated with cyclin-dependent kinase p34 CDC2 , and that its kinase activity increased through phosphorylation by p34 CDC2 -cyclin B1 (Badea et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the MAC, RGC-32 protein shows complex formation with cyclin B1/CDC2, stimulating the cell cycle in rat oligodendrocytes (58) and human aortic smooth muscle cells (59). Upregulation of RGC-32 mRNA and protein is an especially noteworthy effect given the widespread presence of RGC-32 in cancer.…”
Section: Complement Promotes Oncogenesismentioning
confidence: 99%